2002
DOI: 10.1002/1521-3773(20020415)41:8<1419::aid-anie1419>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recognition of Fluoride Anion Using a Li+-Metallacrown Complex

Abstract: A redox‐responsive receptor based on a self‐assembled metallamacrocycle is able to selectively bind molecular LiF (see X‐ray crystal structure) and act as a highly selective chemosensor for the detection of fluoride anions by electrochemical means, even in protic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Complexes with Ligand N -(2-Pyridylmethyl)- l -alanine. A variety of MCs are known; however, only a few structural examples have been reported for [12-MC-3]. Recent work by Severin et al has shown that an organometallic analogue [12-MC-3] has been found to be a highly potent ionophore with remarkable affinity for Li + and Na + 12b,4a,, …”
Section: Resultsmentioning
confidence: 99%
“…Complexes with Ligand N -(2-Pyridylmethyl)- l -alanine. A variety of MCs are known; however, only a few structural examples have been reported for [12-MC-3]. Recent work by Severin et al has shown that an organometallic analogue [12-MC-3] has been found to be a highly potent ionophore with remarkable affinity for Li + and Na + 12b,4a,, …”
Section: Resultsmentioning
confidence: 99%
“…300,301 While the trinuclear Ru(III) metallomacrocycles ( 256 , Figure 28) showed high affinity and selectivity for Li + and Na + ion, 164,302 the Ir(III) macrocycles act as a fluoride ion receptor in which a pre-coordinated lithium ion serves as the binding site. 303 The quantification of the host-guest complexes were done by NMR, electrochemical and colorimetric methods. Extending the same strategy further, they have also designed and synthesized a Ru-based metallomacrocycle for the selective detection of lithium ions in water and in serum by fluorescence spectroscopy.…”
Section: Two-dimensional (2d) Ensemblesmentioning
confidence: 99%
“…Molecular containers are of continuing interest for synthetic chemists due to their realized uses as catalysts, , sorters, sensors, , and in cavity directed synthesis. , Most molecular containers are based on hydrocarbon frameworks . An advantage of inorganic frameworks is their potential rigidity, which should impart size-based selectivity to these supermolecules .…”
Section: Introductionmentioning
confidence: 99%